2016
DOI: 10.1021/acs.jnatprod.6b00641
|View full text |Cite
|
Sign up to set email alerts
|

Stachybotrysin, an Osteoclast Differentiation Inhibitor from the Marine-Derived Fungus Stachybotrys sp. KCB13F013

Abstract: Two new phenylspirodrimane derivatives, stachybotrysin (1) and stachybotrylactone B (2), were isolated from the cultures of the marine-derived fungus Stachybotrys sp. KCB13F013. The structures were determined by analyzing the spectroscopic data (1D and 2D NMR and MS) and chemical transformation, including the modified Mosher's method and single-crystal X-ray structure analysis. Compound 1 exhibited an inhibitory effect on osteoclast differentiation in bone marrow macrophage cells via suppressing the RANKL-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…KCB13F013 (Wi Island, South Korea, the Yellow Sea). Stachybotrysin exhibited an inhibitory effect on osteoclast differentiation in bone marrow macrophage cells via suppressing the RANKL-induced activation of p-ERK, p-JNK, p-p38, c-Fos, and NFATc1 [135].…”
Section: Discussionmentioning
confidence: 96%
“…KCB13F013 (Wi Island, South Korea, the Yellow Sea). Stachybotrysin exhibited an inhibitory effect on osteoclast differentiation in bone marrow macrophage cells via suppressing the RANKL-induced activation of p-ERK, p-JNK, p-p38, c-Fos, and NFATc1 [135].…”
Section: Discussionmentioning
confidence: 96%
“…In 2016, Jong Won Kim et al reported the discovery of stachybotrysin ( 29 , Figure 11), which was isolated from the marine fungus Stachybotrys sp. KCB13F013 and found to inhibit the RANKL-induced activation of p-ERK, p-JNK and p-p38 MAPK [50]. The kinase inhibition activities of compound 28 and 29 were determined by Western blot analyses.…”
Section: Discussionmentioning
confidence: 99%
“…terpenoid scalaradial (250) [275]; fungus Stachybotrys sp. KCB13F013 meroterpenoid stachybotrysin (251) [276]; soft coral Clavularia sp. terpenoid stolonidiol (252) [277]; cyanobacterium Lyngbya sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%
“…pyrroloiminoquinone alkaloid discorhabdin L (275) [297]; sponge Dysidea sp. polybrominated diphenyl ether 3,4,5-tribromo-2-(2 ,4 -dibromophenoxy)-phenol (276) [298]; sponge Dysidea sp. tetracyclic meroterpene dysiherbol A (277) [299]; sand dollar Scaphechinus mirabilis aminonaphtho-quinone echinamine B (278) [300]; sponge derived fungus Stachylidium sp.…”
Section: Marine Compounds With Miscellaneous Mechanisms Of Actionmentioning
confidence: 99%